Historiography Researchof K.Ventsel’s Creative Heritage - Gonchar, Inna (Pedagogical Discourse, 2013)
The analysis ofK.Ventsel’s creative heritage has been carried out in thearticle. On the basis of chronological approach, scientific researchhas beensystematized by the authoras a result of which three main stages of historiography research have beenidentified. It was found that within the first stageK.Ventselʼsideas were taken biased,perceived, prejudiced, ideologysed, so that their coverage have been subjected to considerable changes. The second stage is characterized by expanding the range of thescientistcreative heritage research, the first attempts to evaluateobjectively and rethink the teacher’sopinions. Within the third phase K.Ventselʼs pedagogywas revived, an objective assessment of his ideas has been done, his name wasreturned to a plead of outstanding teachers of the late XIX - early XX century.